Therapist Factors and Outcomes in CBT for Anxiety in Youth - Podell, Jennifer L. (Prof Psychol Res Pr, 2013)
This study examined the relationship between therapist factors and child outcomes in anxious youth who received cognitive–behavioral therapy (CBT) as part of the Child–Adolescent Anxiety Multimodal Study (CAMS). Of the 488 youth who participated in the CAMS project, 279 were randomly assigned to one of the CBT conditions (CBT only or CBT plus sertraline). Participants included youth (ages 7–17; M = 10.76) who met criteria for a principal anxiety disorder. Therapists included 38 cognitive–behavioral therapists. Therapist style, treatment integrity, and therapist experience were examined in relation to child outcome. Child outcome was measured via child, parent, and independent evaluator report. Therapists who were more collaborative and empathic, followed the treatment manual, and implemented it in a developmentally appropriate way had youth with better treatment outcomes. Therapist “coach” style was a significant predictor of child-reported outcome, with the collaborative “coach” style predicting fewer child-reported symptoms. Higher levels of therapist prior clinical experience and lower levels of prior anxiety-specific experience were significant predictors of better treatment outcome. Findings suggest that although all therapists used the same manual-guided treatment, therapist style, experience, and clinical skills were related to differences in child outcome. Clinical implications and recommendations for future research are discussed.